Heidegger’s Spectral Abyss: Grounding the (Strange) Return of the Subject and Object in the Žižek & Harman Duel/Duet - Kahambing, Jan Gresil (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
The split between the subject and object is the epistemological inheritance of modernity’s enchantment with substance, notably shown by the subjectivism in the Cartesian ‘cogito’ and Kantian ‘transcendental I’. In this paper, I will attempt to argue that despite Heidegger’s ontological hermeneutics that eclipsed Descartes’ dualism and Kant’s transcendentalism, there is still a possibility of the return of both Subject and Object – exemplified even on ontological grounds in Žižek’s Subject-Oriented Ontology and Harman’s Object-Oriented Ontology. Conveniently, I will situate the two ontologies, dubbed respectively as SOO and OOO, in the recent Žižek & Harman Duel/Duet (2017). Further, I will rework the uses of two important notions found only in this debate – unhintergebar (the ‘unsurpassable’) and ostranenie (defamiliarization) – to explicate the transport from Heidegger’s metaphysical abyss to spectral abyss. Arguing from Heidegger’s ground (grund) and/or abyss (abgrund) that grounds possibilities of being, I will call this new ground for strange possibilities as spectral abyss (gespenstisch abrund). To achieve this, I will do two things. First, I will briefly rehearse the epistemological split and Heidegger’s ontological turn. And second, I will resituate the debate by showing how Žižek and Harman’s ontologies can emerge from Heidegger’s spectral abyss. My ultimate goal is then to explicate not the return but the ground that makes it possible for a strange return.